Inside Cover. Issue 12 (22nd December 2020) - Lilge, Lothar; Manalac, Angelica; Weersink, Madrigal; Schwiegelshohn, Fynn; Young‐Schultz, Tanner; Abdalrhman, Abdallatif Satti; Wang, Chengjin; Ngan, Aldrich; Gu, Frank X.; Betz, Vaughn; Hofmann, Ron
Abstract: Access to sterile personal protective equipment, in particular for filtered face respirators is critical in the current pandemic for front line healthcare workers. Extended use may be required during supply shortages or due to economic considerations. UVC sterilization can be a cost‐effective technique capable of high throughput. The suitability of various N95 respirator designs for UV mediated reuse were evaluated based on the materials utilized. (Background image: with permission from Prescient x . Virus image: Sophia Lilge. Further details can be found in the article by Lothar Lilge, Angelica Manalac, Madrigal Weersink, Fynn Schwiegelshohn, Tanner Young‐Schultz, Abdallatif Satti Abdalrhman, Chengjin Wang, Aldrich Ngan, Frank X. Gu, Vaughn Betz, Ron Hofmann (e202000232 ). Abstract : Access to sterile personal protective equipment, in particular for filtered face respirators is critical in the current pandemic for front line healthcare workers. Extended use may be required during supply shortages or due to economic considerations. UVC sterilization can be a cost‐effective technique capable of high throughput. The suitability of various N95 respirator designs for UV mediated reuse were evaluated based on the materials utilized. (Background image: with permission from Prescient x . Virus image: Sophia Lilge. Further details can be found in the article by Lothar Lilge, Angelica Manalac, Madrigal Weersink, Fynn Schwiegelshohn, Tanner Young‐Schultz, Abdallatif Satti Abdalrhman, Chengjin Wang, Aldrich Ngan, Frank X. Gu, Vaughn Betz, Ron Hofmann (e202000232 ).